COORDINATION AND SUPERVISION OF POLICE INVESTIGATIONS OF CRIMINAL INVESTIGATION PROCESS CARRIED OUT BY CIVIL SERVANT INVESTIGATIONS - Supiyanto, Asep; Wahyuningsih, Sri Endah (Jurnal Hukum Khaira Ummah, 2023)
Coordination and Controlling function of the Police Investigators on the process of criminal investigations by the Civil Servant Investigators has been regulated in the Criminal Law Code of Criminal Procedure, Law of the Republic of Indonesia Number 2 of 2002 on the Indonesian National Police, and the Regulations of the Indonesian National Police Chief number 6 of 2010 concerning investigations management by the Civil Servants investigators and the Regulation of the Indonesian National Police Chief number 20 of 2010 on Coordination, Supervision and Development Investigations for Civil Servants Investigators. Coordination activities include notification of commencement of the investigation, providing investigative assistance to the civil servants Investigator (in the form of technical assistance, tactical aid, relief efforts to force, and consulting assistance), submission of case files, the transfer of suspects and material evidence, termination of the investigation, information exchange, regular meetings, and joint investigations. While controlling function includes to attend and give instructions in case the title is held civil servant investigator, ask for and examine the progress of the investigation report of the civil servant investigators, examine the results of the investigation file and then going to the General Prosecutor, with the ranks of supervision civil servant investigators as requested by agency investigators led civil servants, perform data collection on the number of civil servant investigator, institution and area of assignment civil servant investigator, handling the case made by the civil servant investigators and aid the investigation, and analyze and evaluate the implementation of the investigation by the civil servants investigators. In practice in the field, coordination and controlling function does not ensure an optimal, even in defiance of regulations. Keywords: Coordination, Controlling and Investigation.